The treatment of landfill leachate over Ni/Al2O3 by supercritical water oxidation - Civan, Ferda; Ozaltun, Demet H.; Kipcak, Ekin; Akgun, Mesut (ELSEVIER, 2015)
This study presents the findings of our research regarding the catalytic treatment of landfill leachate over Ni/Al2O3 by supercritical water oxidation. Hydrogen peroxide was used as the oxygen source. The experiments were carried out at a constant pressure of 25 MPa, in the temperature range of 400-600 degrees C and the reaction time range of 30-150 s. The effects of temperature, reaction time, pressure, catalyst and oxidant use on the total organic carbon and total nitrogen contents of the liquid effluents were examined. As a result, it was seen that supercritical water oxidation was a very effective method for the treatment of landfill leachate. Treatment efficiencies up to 98.2% in terms of total organic carbon conversion were obtained. However nitrogen removal achieved about 57% in terms of total nitrogen conversion. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Catalyst; Landfill leachate; Ni/Al2O3; Supercritical water oxidation; Treatment; WASTE-WATER; FENTON; Chemistry; Engineering